Numerical Investigation of Carbon Fiber Reinforced Polymer Confined Concrete-Filled Steel Tube Columns under Eccentric Load - Brhanu Degefa Zewdu; Temesgen Wondimu Aure (Advances in Civil Engineering)
Recently, Fiber Reinforced Polymer (FRP) materials have emerged as a viable alternative to confined columns due to their high ultimate tensile strength to weight ratio and corrosion resistance under harsh and corrosive environments. Many previous studies were focused on the confining capability of FRP on concentric axial loads. This study presents a nonlinear finite element (FE) investigation of the effects of the thickness of Carbon Fiber Reinforced Polymer (CFRP), the thickness of steel tube, cross-sectional shape, and slenderness effect of an FRP confined concrete-filled steel tube (FCCFST) column under eccentric load. The FE model was validated by comparing the results with experimental data available in the literature, and good agreement was found. From the FE results, it was found that the steel tube and CFRP confinement improved the load resistance capacity by about 34% to 39%, and the axial shortening of the column at the peak load, from 136% to 57%, in rectangular and circular cross-sections, respectively. The efficiencies of steel tube and CFRP confinement first increase with an increasing eccentricity of the axial load and then start to decrease as the failure mode of the column changes to stability.